Environmental Governance Challenges of Indigenous Forest Recognition: Climate Solution Ideal and Its Uneven Outcomes in Indonesia - Abdullah, Abdurrahman; Fisher, Micah R.; Sahide, Muhammad Alif K. (Forest and Society, 2024)
Formal policies on Indigenous land and forest rights recognition are increasingly being promoted as a climate solution in global forums. While this suggests a clear discursive victory for environmental justice movements, there has been less attention on the aftermaths of recognition. This in part owes to the novelty of policies on Indigenous land and forest recognition, but also due to the tendency among proponents to view formal legal victories as a means and ends of advocacy. In this paper, we spotlight what happens after recognition in Kajang, the site of the first Indigenous community to formally regain authority over state forests in Indonesia. We apply a lens from political ecology and draw from critical research on land and property to identify the unevenness of an emerging climate policy solution. Through grounded village-level research engagements lasting over three years in the span of over a decade, we identify a range of ethnographic perspectives on land, resources, authority, and shifting identity formation. Results highlight three main findings. First, while the assumption of community-based initiatives presumes the restoration of rights, new forms of enclosure and marginalization occur vis-à-vis policies of Indigenous land rights recognition. Second, the assumption of forest and environmental stewardship is by no means automatic, as land and resource concerns have a geographic dimension that may result in protection for some forests at the expense of others. Finally, Kajang is unique for its history and political economy making it difficult to assume parallel outcomes elsewhere. While environmental justice movements should continue to advocate for Indigeneity and forest and land recognition, more attention should be given to their underlying strategies and the implications of doing so.